Accelerated Ovarian Aging Among Type 2 Diabetes Patients and Its Association With Adverse Lipid Profile - Wang, Yahao; Wang, Yangang (Frontiers in Endocrinology, 2022)
Background The impact of diabetes on reproductive function is still not clearly defined. This study aimed to evaluate accelerated ovarian aging in women with type 2 diabetes mellitus (T2DM) and its association with adverse lipid profile. Methods Female patients with T2DM (n=964) and non-T2DM controls (n=263) aging from 18-80 years were included. Levels of circulating sex hormones were measured at the follicular phase in menstruating women. We analyzed the age-specific trends in the levels of sex hormones between T2DM and controls. The correlations of sex hormones with the lipid profile, including low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC) and triglycerides (TG) were also evaluated. Results In the temporal trends analysis, LH and FSH both started to increase obviously approximately from the age of 45 years among patients with T2DM, and displayed peaks of LH and FSH among patients with T2DM aged between 61 and 65, both of which were obviously earlier than that in non-T2DM controls and proved the accelerated ovarian aging among patients with T2DM. E2 of patients with T2DM was continuous lower than that of non-T2DM controls from approximately 45 years old, and LH and FSH of patients with T2DM were higher than those of non-T2DM controls between the age of 55 to 65 years. Multiple linear regression analyses revealed that LH was positively correlated with LDL-C (Coefficient=0.156, P=0.001) and TC (Coefficient=0.134, P=0.025), and was negatively correlated with HDL-C (Coefficient =-0.065, P=0.001) in patients with T2DM aged between 51 and 60, which was independent of age, T2DM duration, body mass index (BMI), glycosylated hemoglobin (HbA1c), FSH, E2 and other potential confounders. Higher E2 level was significantly and independently correlated with lower LDL-C (Coefficient= -0.064, P=0.033) in patients with T2DM aged between 51 and 60. Conclusions This study suggests that patients with T2DM have accelerated ovarian aging, and it is correlated with the occurrence of disturbed lipid profile in patients with T2DM. With an ever increasing number of female patients with T2DM diagnosed at younger ages, the accelerated ovarian aging and its adverse impacts in T2DM need to be carefully managed.